ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA PT SAHABAT AGRO MAKMUR SEJAHTERA PALU - Ririn, Ririn Parmita; Fitriana; Ririn Parmita (Jurnal Unicorn ADPERTISI, 2024)
This study aims to determine whether of merchandise inventory has been implemented or not, and also to determine the implementation of the internal control system of inventory at PT. Friends of Agro Makmur.The method used is qualitative research. Data analysis techniques using the model of Miles and Huberman (1994) namely data collection, data reduction, data presentation, and conclusions. The results of the study: (1) Implementation of internal control of merchandise inventory at PT. Friends of Agro Makmur Sejahtera Palu have been implemented and are running quite well because they are supported by the Zahir computerized system that assists management in carrying out internal control, and (2) HR policies and training, management philosophy and operating models as well as organizational structures and delegation of authority and responsibility need to be evaluated and made in writing. Monitoring Risks that are not maximal have an impact on employee recruitment not in accordance with skills and educational background. Concurrent work tasks are excessive, but information and communication are quite effective because they are monitored directly by the leader and every morning breaving is always done.